MAIN TRENDS IN DEVELOPMENT OF THE FINANCIAL INVESTMENTS IN UKRAINE - Sholudko , О.; Hrytsyna , О.; Syniavska , Л.; Bohach , М. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
Financial investments play an important role in stimulating economic growth, creating jobs, and attracting investments. It is a mechanism that boosts various sectors of the economy and maintains a sustainable growth of the national GDP. The article examines the impact of financial investments on the growth of the national economy, job creation, and investments attraction, analyses the effect of technological progress and innovations on the development of financial investments; investigates the use of financial technologies (FinTech) and digital tools in financial services and the process of financial investing. The main risks associated with financial deposits, such as the risk of capital loss, inflation risk, liquidity risk, etc, are defined. The protective measures that are taken to reduce these risks and ensure the safety of depositors are studied. New trends and prospects in the field of financial investments in Ukraine, such as development of social investment, environmental financing, microfinancing, and investments in startups, were analyzed, as well as the opportunities they provide for investors and economy were considered. Technological progress also affects the analysis and management of risks in financial investments. With increased access to data and improved analytical tools, investors can more objectively assess the risks and make better-informed capital allocation decisions. The increasing volume of the financial component in investments is one of the promising directions for development of the country and its competitiveness at the international market, whilst financial investments are the important tool for development of the state economy and finances as they contribute to increasing the amount of investments that are necessary for the growth of economic sectors.